MİYASTENİYA GRAVİS TANILI OLGULARDA HLA TİPLEMESİ - AKALIN, Mehmet; ALTINTAŞ, Ayşe; YILMAZ, Erkan; ERKOL, Gökhan; ERDOĞAN, Ergun; BASLO, Perihan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The aim of this study was to investigate HLA phenotype frequencies and associations in myasthenia gravis patients considering sex, antibody titer, thymic pathology, age of onset, clinical type and try to understand immunogenetic basis for myasthenia gravis in Turkey. HLA phenotypes were studied in 30 patients (18 female, 12 male) with myasthenia gravis (MG) and 214 healthy controls, using standard microcytotoxicity assay. Results.- When compared with the control group, all MG patients showed significant increase in HLA-B38(16) (odds ratio (OR): 8.08 and p< 0.005), HLA-DR1 (OR:3.31 and p< 0.05) HLA-DQ2 (OR:14.07, p<0.005), DQ4 (OR:2.47, p<0.05) and DQ7(3) (OR: 3.35, p<0.005), but these results lost significance when corrected p value used. No association with HLA phenotypes was found considering level of antibody titer, thymic pathologies, and age of onset. Conclusion.- These findings may provide some information for future studies on the immunogenetic basis of myasthenia gravis.